PRODUCTION AND POTENCY OF LOCAL RAMBUTAN AT EAST JAVA AS A CANDIDATE PHYTOPHARMACA - Lestari, Sri Rahayu; Djati, Muhammad Sasmito; Rudijanto, Ahmad; Fatchiyah, Fatchiyah (AGRIVITA, Journal of Agricultural Science, 2013)
Rambutan is a tropical fruit that grow well in Indonesia and the peel is considered as waste. Many researchersâ showed that rambutan peel contains polyphenol that could be expected to avoid obesity.Â  The objective of this study was to explore the increasing production of local rambutan and to identify the promising phytochemical compounds on its peel as phytopharmaca candidate against obesity. Survey was conducted on the production of rambutan, potential plantation area, and marketing. Sample of rambutan peel collected from the sub-district Kanigoro, Blitar. Phytochemical compounds were analyzed using TLC, HPLC and FT-IR. Bioassay analysis used obesity rat models. The survey result showed a mean of rambutan production increased 2,6% in 2007-2012. Average production of rambutan 70-120 kg/tree. Vegetative multiplication usually done to maintenance of rambutan quality. The main compound ofÂ  Rambutan peelÂ  extract (RPE) is flavonoids, tannins, ellagic acid and the major functional group of CH3, aliphatic CH3, and C=O. These compounds have a potential activity against obesity.Â  RPE 30 mg/kgBW dose was significantly inhibit the weight gain of obese rats and reducing the adipocyte size (p<0.05).Key words: potency, production, local rambutan, blitar, obesity